The viability of carbon capture at airports using innovative approaches - Miyoshi, Chikage; Zhu, Mingming; Burgess, Paul J.; Girkin, Nicholas T.; Clough, Peter T. (Cranfield University, 2022)
This report examines the feasibility and opportunities for carbon capture, use and storage (CCUS) at airports using innovative new technologies. CCUS provides a range of approaches that could help airports to move towards net zero greenhouse gas (GHG) emissions. CCUS technologies can be categorised into those that depend on engineering, and those that are nature-based. The feasibility and opportunities of both approaches were examined in the context of four case study airports, using GHG emissions data from 2019.
Prepared for Société Internationale de Télécommunications Aéronautiques (SITA) https://www.sita.aero/
Keywords: air transport decarbonisation; sustainable aviation; airport; carbon capture; nature based solutions; case study